The Influence of Influencer Credibility on Skincare Product Purchase Intention through Trust in Influencers as a Mediating Variable Among TikTok Shop Users in Padang City - Yohana Destia Hafifah; Vidyarini Dwita (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The quick expansion of social commerce via TikTok Shop has led businesses to use influencers as a way to promote products and increase the likelihood that consumers will make purchases. This research investigates how influencers' credibility affects the intention to buy skincare products, with a focus on trust in influencers as an intermediary factor among residents of Padang City. This study used a quantitative method, specifically a survey, involving 144 TikTok users who had viewed influencer content about skincare products. The study employed purposive sampling as the method for selecting participants, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of the SmartPLS 4 software. The findings show that influencer credibility has a positive and significant impact on trust in influencers (β = 0.752; p < 0.001) as well as on the intention to make a purchase (β = 0.474; p < 0.001). There is a positive and significant relationship between trust in influencers and the intention to make a purchase, (β = of 0.428 and p < 0.001). Additionally, it was found that trust in influencers partially mediated the link between influencer credibility and purchase intention (β = 0.322; p < 0.001). This suggests that influencer credibility can boost purchase intention both directly and indirectly by building greater consumer trust. Therefore, when consumers perceive a higher level of credibility in an influencer, they tend to trust that influencer more and are more likely to intend to buy skincare products that are promoted on TikTok Shop.